The use of Internet applications in managing logistics activities among palm oil industry participants - Kamarulzaman, Nitty Hirawaty; Mohd Nawi, Nolila (Faculty of Economics and Management, Universiti Putra Malaysia, 2009)
With the advancement of Internet technologies, many companies have adopted the use of the technologies to improve the efficiency and effectiveness of their activities. This paper aims to investigate the utilization of Internet technologies in the Malaysian Palm Oil Industry (MPOI) and explore how the technologies have been exploited by the palm oil industry participants to manage their logistics activities. The respondents of the study were the MPOI participants involved in Internet-based activities. The findings revealed that Internet applications were still new and at an early stage. Many participants did not realise the potential of advanced Internet technologies in managing their business activities. Lack of understanding of advanced Internet technologies explains the low level of utilization of these technologies among the MPOI participants. Most of the participants were comfortable with conventional ways of managing their logistics activities.